No todos somos ya periodistas. Un análisis de la utopía del periodismo ciudadano desde la perspectiva del reportaje interpretativo - Maciá Barber, Carlos (Estudios sobre el Mensaje Periodístico, 2007)
The citizen journalism it conforms at present as a recovery of the access of the citizenship to the mass media. This reformulation of the active participation of the public ones in the informative process concerns in a direct way different fields of the journalistic activity: the nature of the journalism, the professional training of the reporter, the labour with the sources, the structure and organization of the mass media, the preceptive of the journalistic genres and the journalistic ethics. His advent, and perhaps his consolidation, intensifies the need to explain, in every case, the benefits and prejudices that his irruption provokes in the professional job and in the own society. Now, in the practice, the interpretive report is a journalistic genre difficultly attainable for the common one of the citizens.